A Compatible Family of Bitstream Watermarking Schemes for MPEG-Audio - Neubauer, Christian; Kulessa, Ralph; Herre, Jürgen (110th AES Convention, 2001)
Audio watermarking enables the robust and imperceptible transmission of data within audio signals. Among the many possible applications of this technique, a number of scenarios require direct embedding of watermarks into a compressed signal representation. Such bitstream watermarking systems enable e.g. on-the-fly embedding of transaction specific data at the time of content delivery via the Internet. This paper extends previous work on bitstream watermarking for MPEG-2/4 Advanced Audio Coding (AAC) towards a compatible family of watermarking schemes for MPEG-1/2 Layer-3 (MP3), MPEG-2/4 AAC and uncompressed audio. Regardless of the format used during data embedding, the same watermark extractor can be employed to recover the embedded message. Both the underlying concepts and relevant experimental results for these schemes are described.<br
herre_papers_audio_watermarking
Keywords: Watermarking; Internet Audio